A comparative study of the relationship some Elkinmetekih variables and electrical activity (EMG) for the most muscle working in the snatch on both sides of the body of the Turkish World Raba Sager Tanner - shaboot ibrahim, Ali (Journal of Physical Education, 2012)
The aim of the study was to determine the values of the difference in the path of gravity on both sides of a column of gravity as well as the proportion of variation in muscle work between both sides of the body's muscles working is important to know the reason for this difference to work on avoided and direct sports about the formula through which the economy effort and the achievement of dignity, have tried to researcher study kinematics variables by video analysis of one of the world champions of weightlifting as well as the measurement of electrical muscle of some of the muscles involved in the snatch for both sides of the body to find out the reasons that are different variables to weight barbell trajectory.